2015
DOI: 10.1111/hex.12402
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family involvement in adult critical and intensive care settings: a scoping review

Abstract: BackgroundDespite international bodies calling for increased patient and family involvement, these concepts remain poorly defined within literature on critical and intensive care settings.ObjectiveThis scoping review investigates the extent and range of literature on patient and family involvement in critical and intensive care settings. Methodological and empirical gaps are identified, and a future agenda for research into optimizing patient and family involvement is outlined.MethodsSearches of MEDLINE, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
213
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(224 citation statements)
references
References 156 publications
(272 reference statements)
5
213
0
6
Order By: Relevance
“…8 Effective implementation of active family engagement begins with the endorsement of the bedside nurse. We must understand how nurses view family engagement and the barriers they face when working to involve family members in patient care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Effective implementation of active family engagement begins with the endorsement of the bedside nurse. We must understand how nurses view family engagement and the barriers they face when working to involve family members in patient care.…”
Section: Resultsmentioning
confidence: 99%
“…8 The results can be used to inform nursing leaders how to target educational and training interventions as well as how to assess resource allocation and policies to reduce barriers to promote nurse support of active family engagement in the ICU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These encounters involved both members of the healthcare team as well as family members and other patient caregivers (eg, close friend). While family members and caregivers are often not considered in collaboration research, new and emerging research has suggested this is an important avenue for future research exploring patient safety and quality of care 14. In this paper, we share the analysis of our findings to highlight the important information revealed through these events, as well as their significance for improving collaboration and ultimately, quality of care.…”
Section: Introductionmentioning
confidence: 91%
“…The difficulty to accept the situation for caregivers as well as the difficulty to define a clear prognosis could explain the negative (or the no evaluation) answer for this item of the questionnaire (DeVoe, Wallace, & Fryer, 2009;Dou, Gao, Lu, & Chang, 2014;Olding et al, 2016;Tsetsou, Oddo, & Rossetti, 2013 However, future studies are needed including a monitoring with standardized clinical scale scores and a larger sample than the one involved for this pilot research in order to compare different models.…”
Section: Discussionmentioning
confidence: 99%